The Evaluation Of Writing Exercises Of English Textbook Entitled "Contextual English 1" Based On School - Based Curriculum - Nuria, Ida (2012)
There are many books that claimed that they are suitable with the School-Based Curriculum. Based on the statement, the writer wants to analyze if the textbook "Contextual English 1" is compatible with the School-based Curriculum or not. In this research the writer focuses on the writing exercises. The aims of this research are to describe whether or not the writing exercises are compatible with those required in School-based Curriculum, and to describe whether or not the writing exercises facilitate the students to achieve the competency. In analyzing the textbook, the writer uses descriptive research and the data are exercises that are taken in Contextual English 1. The writer collects the data by reading the English textbook, and than classifies the exercises containing writing exercises. The results of this study show that the percentage for the writing exercises developed in "Contextual English I" based on the percentage, referring to schema of quality classification proposed by Suharsimi (1993) is 77, 78%. Among the nine sub-competencies in School-based Curriculum there are seven subcompetencies that are presented in writing exercises in the textbook that are compatible with School-based Curriculum. From the result of the percentage above the writer concludes that the quality of writing exercises in the textbook is very good in developing writing skill as demanded by the School-based Curriculum, and the second result of this research is the writing exercises of the textbook facilitate the students to achieve the competency of writing.